What, for Lacan, makes the function of the Father work? Of Abraham and the goat, or, of Elliott and ET - Hook, Derek (PINS-Psychology in Society, 2024)
Lacan, Jacques (2013) On the Names-of-the-Father. (Edited by Jacques-Alain Miller, Translated by Bruce Fink.) Cambridge: Polity Press (2005-French). ISBN: 978-0-7456-5991-6 hbk. Pages 105. What Lacan calls the Name-of-the-Father refers to the influence of cultural and social law within the family, something which has traditionally – especially within patriarchal societies – been associated with the actual figure of the father. Given that Lacan thinks of the Name-of-the-Father as a signifier – and a crucial signifier at that, one that anchors the symbolic order and enables it to function – it need not refer to a literal father. This much is made clear by the reference in Catholicism to, precisely, the Name of the Father, a signifier (or term of reference), which clearly points beyond the level of mere mortal fathers. Stijn Vanheule (2011) provides a brief yet illuminating description of the Lacanian concept of the father. The father for Lacan is “a symbolic function to which all group members … are subjected” (61); “It provides human beings with an internalized compass of culturally and socially viable principles” (Stijn Vanheule, 2011: 61).